Peculiarity of Rh bulk diffusion in La-doped alumina and its impact on CO oxidation over Rh/Al2O3 - Stoyanovskii V. O. Vladimir; Vedyagin A. A. Aleksey Anatolievich; Volodin A. M. Aleksandr; Kenzhin R. M. Roman; Shubin Yu. V. Yury Viktorovich; Plyusnin P. E. Pavel Evgenjevich; Mishakov I. V. Iljya Vladimirovich (2017, 2017)
Title screen